The effectiveness of an emotion-focused educational programme in reducing diabetes distress in adults with type 2 diabetes mellitus at 12-month follow-up: a cluster randomized controlled trial. (May 2019) - Chew, Boon-How; Vos, Rimke C.; Fernandez, Aaron; Shariff Ghazali, Sazlina; Shamsuddin, Nurainul Hana; Ismail, Mastura; Rutten, Guy E.H.M.
Background: Diabetes distress (DD) is an increasingly important part of clinical medicine, diabetes self-management and research topic in people with diabetes mellitus. The present study evaluated the effectiveness of a value-based emotion-focused educational program in Malay adults with type 2 diabetes (VEMOFIT) at 12-month follow-up compared with a program with systematic attention to participants' emotions (attention-control). Methods: VEMOFIT consisted of four biweekly group sessions and a booster session after 3 months; the attention-control program consisted of three sessions over the same period. Intention-to-treat analysis with multilevel mixed modelling was done to estimate the intervention effect. Results: Participants ( n  = 124) randomized to VEMOFIT ( n  = 53) or attention-control ( n  = 71). Mean (SD) age 55.7 (9.7) years, median diabetes duration 7.0 (8.0) years and mean HbA1c level 9.7% (82 mmol/mol). The mean DD (DDS-17 scale) level decreased in both groups (from 3.4 to 3.3 versus 3.1–2.5, respectively), significantly more in the attention-control group [adjusted difference −0.6, 95% confidence interval (CI) −1.1, −0.2]. The VEMOFIT group had a significant improvement in self-efficacy (DMSES, range 0–200; adjusted difference 16.4, 99.4% CI 1.9, 30.9). Other outcomes did not differ. Conclusions: Because the attention-control program resulted in a decreased DD 1 year later, its implementation on a larger scale seems justified. Trial registration: NCT02730078; NMRR-15-1144-24803